Statutory Protection of Creditors of a Subsidiary Company under Ethiopian Law: A Case for Parent Company’s Liability for the Debts of Its Subsidiaries - Sefara, Abdata Abebe; Kefani, Hailemichael Tadesse (Bahir Dar University Journal of Law, 2024)
A corporate group consists of a parent company and subsidiary companies with separate legal personality. A corporate group can have a dominant influence and may drain the assets of member companies toward the parent company, threatening the interests of minority shareholders, and creditors. To safeguard these interests, statutory provisions or self-help mechanisms should provide protection. This article examined the legal frameworks provided by Ethiopian laws for safeguarding the creditors of subsidiary companies in corporate groups. Specifically, it emphasized the question of whether the parent company is liable to a subsidiary companyâ€Ÿs creditors. The Ethiopian Revised Commercial Code (RCC), the primary legislation governing corporations in Ethiopia, establishes general regulations on the protection of creditors of businesses. This article explores the liability of a parent company towards the creditors of its subsidiary under the RCC and other relevant Ethiopian legislations. It uses German Law and the UK Company Act for comparative discussions. Italian law is also consulted. The study reveals that the RCC has provisions which prohibit parent companies from abusing control over subsidiaries. The provisions are related to wrongful trading, abuse of group’s interests to the detriment of its subsidiaries, and cross-holdings of shares above the legal thresholds. These provisions provide statutory protections to creditors of a controlled company in a corporate group. Violations of these prohibitions by a parent company can lead to different degrees of liability towards creditors of a subsidiary company.